Bifunctional Peptide‐Engineered Mitochondria Alleviate Myocarditis and Cardiac Fibrosis by Site‐Specifically Inhibiting NETosis - Hu, Xiankang; Pan, Lina; Chen, Haiyan; Chen, Liyuan; Tang, Yige; Lv, Dingyi; Li, Chenwen; Zhang, Jianxiang; Luo, Suxin (Advanced functional materials, 2025)
Myocarditis is a leading cause of sudden cardiac death and dilated cardiomyopathy in young adults, and effective therapies are urgently needed. Here, it is found that intravenous transplantation of exogenous mitochondria (Mito) significantly attenuates inflammation and oxidative stress in the heart, mitigates myocardial injury, improves cardiac function, and alleviates fibrosis and heart failure in mice with experimental autoimmune myocarditis (EAM). Mechanistically, injected Mito can be internalized by neutrophils and subsequently transported to the inflamed hearts of EAM mice. Following internalization in neutrophils, Mito may induce mitochondrial fusion, restore mitochondrial function, inhibit the mitochondrial permeability transition pore opening, and reduce excessive production of mitochondrial reactive oxygen species. These effects collectively inhibit NETosis, known as the formation of neutrophil extracellular traps (NETs), thereby suppressing inflammation and apoptosis of cardiomyocytes induced by NETs. Notably, these findings demonstrate for the first time that mitochondrial transplantation exert therapeutic effects by regulating neutrophils rather than directly integrating into target cardiomyocytes. Additionally, a combination therapy is developed by engineering Mito with a novel bifunctional peptide possessing anti‐inflammatory and anti‐fibrotic properties, which shows potent synergistic effects in treating myocarditis in mice. This findings provide a new strategy toward innovative mitochondrial‐derived therapies for myocarditis and other autoimmune and inflammatory diseases.